Back to the roots - Grasslin, Thomas
The article discussed how Thomas Grasslin, an entrepreneur, has come up with an unusual business idea: he wants to create a primeval forest for green tourism and artistic events - right at the heart of Europe. He is exploring some surprising ways of financing the project.